New national and regional Annex I Habitat records: from #45 to #59 - Giovanni Rivieccio; Claudia Angiolini; Mattia Martin Azzella; Simonetta Bagella; Gianmaria Bonari; Federica Bonini; Silvia Cannucci; Maria Carmela Caria; Alessandro Crisafulli; Romeo Di Pietro; Assunta Esposito; Emanuele Fanfarillo; et al. (Plant Sociology, 2022)
New Italian data on the distribution of Annex I Habitats are reported in this contribution. Specifically, 8 new occurrences in Natura 2000 sites are presented and 27 new cells are added in the EEA 10 km × 10 km reference grid. The new data refer to the Italian administrative regions of Apulia, Campania, Calabria, Lazio, Tuscany, Umbria, Sardinia, and Sicily.